Targeting angiogenesis in gastrointestinal tumors: strategies from vascular disruption to vascular normalization and promotion strategies angiogenesis strategies in GI tumor therapy - Li, Jiajia; Li, Zhengrui; Wang, Keliang (Frontiers in Immunology, 2025)
Angiogenesis plays a critical role in the progression of gastrointestinal (GI) tumors, making it an important therapeutic target. This review explores recent advancements in targeting angiogenesis for GI tumor therapy, highlighting strategies that range from vascular disruption to vascular promotion. The biological foundation of tumor angiogenesis is discussed, with a focus on the molecular mechanisms that regulate this process, including key players such as VEGF, HIFs, and non-coding RNAs. Current therapeutic strategies, including anti-angiogenic agents, vascular normalization approaches, and emerging vascular promotion therapies, are analyzed for their clinical applications and limitations. Additionally, the review examines combination strategies that integrate anti-angiogenic therapy with chemotherapy, immunotherapy, and other modalities to enhance efficacy and overcome resistance. Despite significant progress, challenges such as drug resistance, tumor heterogeneity, and adverse effects remain. Future research directions emphasize the discovery of novel molecular targets, development of personalized treatments, and innovative combination therapies to optimize outcomes for patients with GI tumors. This comprehensive review provides a foundation for advancing angiogenesis-targeted therapies in GI cancer treatment.